The association between penicillin allergy and surgical site infection after orthopedic surgeries: a retrospective cohort study - Niu, Tong; Zhang, Yuelun; Li, Ziquan; Bian, Yanyan; Zhang, Jianguo; Wang, Yipeng (Frontiers in Cellular and Infection Microbiology, 2023)
Background Cephalosporins are used as first-line antimicrobial prophylaxis for orthopedics surgeries. However, alternative antibiotics are usually used in the presence of penicillin allergy (PA), which might increase the risk of surgical site infection (SSI). This study aimed to analyze the relationship between SSI after orthopedic surgeries and PA among surgical candidates and related alternative antibiotic use. Methods In this single-center retrospective cohort study, we compared inpatients with and without PA from January 2015 to December 2021. The primary outcome was SSI, and the secondary outcomes were SSI sites and perioperative antibiotic use. Moreover, pathogen characteristics of all SSIs were also compared between the two cohorts. Results Among the 20,022 inpatient records, 1704 (8.51%) were identified with PA, and a total of 111 (0.55%) SSI incidents were reported. Compared to patients without PA, patients with PA had higher postoperative SSI risk (1.06%, 18/1704 vs. 0.51%, 93/18318), shown both in multivariable regression analysis (odds ratio [OR] 2.11; 95% confidence interval [CI], 1.26-3.50; p= 0.004) and propensity score matching (OR 1.84; 95% CI, 1.05-3.23; p= 0.034). PA was related to elevated deep SSI risk (OR 2.79; 95% CI, 1.47-5.30; p= 0.002) and had no significant impact on superficial SSI (OR 1.39; 95% CI, 0.59-3.29; p= 0.449). The PA group used significantly more alternative antibiotics. Complete mediation effect of alternative antibiotics on SSI among these patients was found in mediation analysis. Pathogen analysis revealed gram-positive cocci as the most common pathogen for SSI in our study cohort, while patients with PA had higher infection rate from gram-positive rods and gram-negative rods than non-PA group. Conclusion Compared to patients without PA, patients with PA developed more SSI after orthopedic surgeries, especially deep SSI. The elevated infection rate could be secondary to the use of alternative prophylactic antibiotics